1993
DOI: 10.1182/blood.v81.12.3343.bloodjournal81123343
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a bispecific IgG capable of inducing T-cell-mediated lysis of malignant B cells

Abstract: Bispecific monoclonal antibodies (bsabs) recognizing both CD3 and a tumor antigen can redirect T-cell-mediated cytotoxicity toward cells bearing that antigen. Such bsabs have been shown to be more effective than monospecific monoclonal antibodies (MoAbs) at preventing tumor growth in animal models of B-cell malignancy. The current studies describe the production and preliminary evaluation of a bsab designed to induce the lysis of malignant human B cells by human T cells. The bsab was obtained from a hybrid-hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…S7). Similar results were found following addition of a bispecific anti-HLA-DR/anti-CD3 monoclonal antibody developed in our laboratory [11] designated IDT3D (Fig. 6).…”
Section: T Cells Maintain Ctx-mediated Nk Cell Responsessupporting
confidence: 84%
“…S7). Similar results were found following addition of a bispecific anti-HLA-DR/anti-CD3 monoclonal antibody developed in our laboratory [11] designated IDT3D (Fig. 6).…”
Section: T Cells Maintain Ctx-mediated Nk Cell Responsessupporting
confidence: 84%
“…Production and purification of a murine bsIgG that reacts with 1D10 (ϩ) lymphoma cells and human CD3 have been described previously (Link and Weiner, 1993). Briefly, bsIgG was isolated from a hybrid-hybridoma produced by fusing cells that secrete 1D10 (murine IgG 1 -kappa) with cells that secrete OKT3 (murine IgG 2a -kappa).…”
Section: Production Of Bsiggmentioning
confidence: 99%
“…1D10 also binds to normal peripheral blood B cells and monocytes from some individuals (data not shown). Previous studies demonstrated that bsIgG produced from a hybridhybridoma recognizing CD3 and the 1D10 antigen induces T-cellmediated lysis of fresh and cultured malignant B cells bearing the 1D10 antigen (Link and Weiner, 1993).…”
mentioning
confidence: 99%
“…Cloned antigens have been used to generate antibodies with higher affinities or with more useful effector functions, either through their use as immunogens (Chen et al, 1994) or as targets to reshape the antigen-binding site of the original antibody (Stenzel-Johnson et al, 1994), or to generate bispecific antibodies to redirect T-cell-mediated cytotoxicity towards tumor cells (Ferrini et al, 1991 ;Link and Weiner, 1993). Tumor-specific antigens can also be used as recombinant vaccines to prevent tumors in subjects at risk, or to arrest tumor growth in patients at early stages (Hareuveni et al, 1990;Lanzavecchia, 1993).…”
mentioning
confidence: 99%